2022
DOI: 10.1177/02662426221089499
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of team entrepreneurial passion from team helping: An affective events theory perspective

Abstract: Research has acknowledged the outcomes of entrepreneurial passion, but little is known in regard to how it occurs. In this article, we shift the focus to the team level and investigate the emergence of team entrepreneurial passion (TEP) from the team helping perspective. Drawing on affective events theory (AET), we examine how team help-seeking and -giving facilitate TEP. Team-level analyses were performed on data drawn from 487 members of 112 new venture teams in an accelerator for high-technology firms in Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…Accordingly, the concept of "team entrepreneurial passion" (TEP) (Cardon et al, 2017) emerges as an emotional predictor within entrepreneurial teams that may impact entrepreneurial behavior (Qian et al, 2022) and team performance (Santos and Cardon, 2019;Boone et al, 2020). While the current findings demonstrate the importance of TEP in moving forward with their entrepreneurial endeavors (Zhu et al, 2022), comparatively few empirical studies were conducted to explain better the influential role of TEP on team outputs, such as team performance (Su et al, 2022;Boone et al, 2020). Rather, this study sought to investigate the relationship between TEP and the performance of entrepreneurial teams in the early stage of new venture creation.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Accordingly, the concept of "team entrepreneurial passion" (TEP) (Cardon et al, 2017) emerges as an emotional predictor within entrepreneurial teams that may impact entrepreneurial behavior (Qian et al, 2022) and team performance (Santos and Cardon, 2019;Boone et al, 2020). While the current findings demonstrate the importance of TEP in moving forward with their entrepreneurial endeavors (Zhu et al, 2022), comparatively few empirical studies were conducted to explain better the influential role of TEP on team outputs, such as team performance (Su et al, 2022;Boone et al, 2020). Rather, this study sought to investigate the relationship between TEP and the performance of entrepreneurial teams in the early stage of new venture creation.…”
Section: Introductionmentioning
confidence: 62%
“…Such results are valuable as they indicate how TEP of specific role identities would lead the team's effort and passion to drive the expected business outcomes at different stages of entrepreneurship. This is important because previous studies on entrepreneurial passion have either reported average levels of entrepreneurial passion at the individual and team level (Rahman et al ., 2020; Zhu et al ., 2022) or considered only one or two domains of team-level passion in their work (Collewaert et al ., 2016; Boone et al ., 2020). By assessing all three domains of TEP, our results show that the domains of TEP behaved distinctly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst some authors uncovered antecedent factors of TEP (Zhu et al, 2022), other researchers revealed what effects it produces. Amongst these effects, the finding that TEP can lead to improved performance is relevant to this study (Shen and Qian, 2022).…”
Section: Literature Review and Hypotheses Development 21 Entrepreneur...mentioning
confidence: 99%
“…Whilst some authors uncovered antecedent factors of TEP (Zhu et al. , 2022), other researchers revealed what effects it produces.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%